Delaminasi Perekat Polivinil Asetat Berbasis Air Satu Komponen untuk Aplikasi Kayu Keras Ulin dan Merbau: Delamination on Polyvinyl Acetate Water Based Adhesive One Component for Ulin and Merbau Hard Wood Working Application - Retno Indarti; Agustinus Ngatin; Robby Sudarman; Tifa Paramitha; Rony Pasonang Sihombing (KOVALEN: Jurnal Riset Kimia, 2022)
Water-based adhesive was one of the most important media for bonding substrates to one another because of their environmental friendly character. Previously, in the application of hardwood adhesives such as Ulin and Merbau, the type of adhesive used was a two-component system. For this reason, a one-component water-based adhesive was introduced in this study. The advantage of these was environmental friendly and high durability. In this application, delamination was one of the important parameters to determine whether the adhesive used was well penetrated or not. For this reason, delamination will be the main parameter in this study. This research includes the preparation of tools and materials, manufacture of PVA (polyvinyl alcohol) solution, polymerization of polyvinyl acetate by mixing the main raw material of vinyl acetate monomer and PVOH solution using APS (ammonium persulfate) initiator. The polymerization process was carried out at 1 atm pressure and 75oC – 80oC temperature accompanied by stirring with ±500 rpm rotation rate. Final product is a homopolymer PVAc (polyvinyl acetate) with PVOH Z-210 with AAEM (acetoacetoxy ethyl methacrylate) content having an acetoxy functional group. A delamination test was carried out on the final product with a modified test based on Japanese Agricultural Standard 1152 where the product was immersed in water for 360 minutes, then placed in an oven at 40oC for 18 hours. Samples using PVOH with AAEM content have an average delamination rate of 0.67-1.67% while existing products on the market have an average delamination rate of 45.83-52.08%.